2018
DOI: 10.1111/adb.12663
|View full text |Cite
|
Sign up to set email alerts
|

The circadian gene, Per2, influences methamphetamine sensitization and reward through the dopaminergic system in the striatum of mice

Abstract: Drug addiction is a chronic and relapsing brain disorder, influenced by complex interactions between endogenous and exogenous factors. Per2, a circadian gene, plays a role in drug addiction. Previous studies using Per2-knockout mice have shown a role for Per2 in cocaine, morphine and alcohol addiction. In the present study, we investigated the role of Per2 in methamphetamine (METH) addiction using Per2-overexpression and knockout mice. We observed locomotor sensitization responses to METH administration, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The behavioral assay consisted of four phases: habituation, drug treatment, drug abstinence, and drug challenge. The protocol used was in accordance with our previous studies (Custodio et al, 2019; Kim et al, 2018). During the first 2 days, mice ( n =8) were habituated to the apparatus for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The behavioral assay consisted of four phases: habituation, drug treatment, drug abstinence, and drug challenge. The protocol used was in accordance with our previous studies (Custodio et al, 2019; Kim et al, 2018). During the first 2 days, mice ( n =8) were habituated to the apparatus for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The conditioned place preference (CPP) and self‐administration (SA) paradigms are experimental procedures widely used to investigate the abuse potential of drugs by characterizing their rewarding and reinforcing effects 12 . The CPP gauges the rewarding value of a drug by measuring the time spent in a drug‐paired compartment versus the time spent in a vehicle (VEH)‐paired compartment 13–15 . Moreover, the SA test assesses the reinforcing effects of a drug by counting the lever responses resulting in drug infusion 16 .…”
Section: Introductionmentioning
confidence: 99%
“…12 The CPP gauges the rewarding value of a drug by measuring the time spent in a drug-paired compartment versus the time spent in a vehicle (VEH)-paired compartment. [13][14][15] Moreover, the SA test assesses the reinforcing effects of a drug by counting the lever responses resulting in drug infusion. 16 Generally, drugs that stimulate the mesolimbic dopamine system induce CPP and/or SA.…”
mentioning
confidence: 99%
“…MAO is rhythmically expressed in wild-type larvae and upregulated in per1b mutant larvae (Huang et al 2015). Kim et al studied the influence of Per2 in cases of methamphetamine addiction and observed that Per2-overexpressed mice presented lower dopamine levels compared to Per2-knockout mice, suggesting that Per2 may influence the addictive effects of methamphetamine through the dopaminergic system (Kim, 2019). Bussi et al studied interval timing (duration discrimination within the seconds-to-minutes range), which involves the dopaminergic-glutamatergic pathway.…”
Section: Discussionmentioning
confidence: 99%